Botulinum Toxin A for Controlling Obesity - Pero, Raffaela (Toxins (Basel), 2016)
Rapid growth of the overweight population and the number of obese individuals in recent decades suggests that current strategies based on diet, exercise, and pharmacological knowledge are not sufficient to address this epidemic. Obesity is the result of a high caloric intake and energy storage, not counterbalanced by an equally important energy expense. Botulinum toxin type A (BoNT-A) use is rapidly expanding to include treatment of a variety of ophthalmological, gastrointestinal, urological, orthopedic, dermatological, secretory, painful, and cosmetic disorders. Many studies evaluating the effect of BoNT-A in gastric antrum e/o fundus for the treatment of obesity have been published. This treatment modality was based on the observation that gastric injection of BoNT-A in laparatomized rats induced a significant reduction of food intake and body weight. These studies have been published yielding debated results. Differences in the selection of patients, the doses of BoNT-A, the method of administration of the toxin, and the instruments of evaluation of some parameters among these studies may be the cause. In this review, it will study the state-of-the-art use of BoNT-A in obesity basic science models and review the clinical evidence on the therapeutic applications of BoNT-A for obesity.